Pediatric cannabis intoxication trends in the pre and post-legalization era. (2nd January 2022) - Cohen, Neta; Galvis Blanco, Laura; Davis, Adrienne; Kahane, Alyssa; Mathew, Mathew; Schuh, Suzanne; Kestenbom, Inbal; Test, Gidon; Pasternak, Yehonatan; Verstegen, Ruud H. J.; Jung, Benjamin; Maguire, Bryan; et al.
Abstract: Introduction: On April 13, 2017, a bill to legalize cannabis was introduced to the Canadian Parliament and presented to the public. On October 17, 2018, Canada legalized recreational cannabis use. We assessed intoxication severity, reflected by ICU admission rates, risk factors and other characteristics in children who presented to the emergency department (ED) with cannabis intoxication, before and after legalization. Methods: A retrospective cohort study of children 0–18 years who presented to a pediatric ED between January 1, 2008 and December 31, 2019 with cannabis intoxication. The pre-legalization period was defined from January 1, 2008 to April 12, 2017 and the peri-post legalization period from April 13, 2017 to December 31, 2019. Results: We identified 298 patients; 232 (77.8%) presented in the pre legalization period and 66 (22.1%) in the peri-post legalization period; median age: 15.9 years (range: 11 months–17.99 years). A higher proportion of children were admitted to the ICU in the peri–post legalization period (13.6% vs. 4.7%, respectively; p  = .02). While the median monthly number of cannabis-related presentations did not differ between the time periods (2.1 [IQR:1.9–2.5] in the pre legalization period vs. 1.7 [IQR:1.0–3.0] in the peri-post legalization period; p =  .69), the clinical severity did. The proportions of children with respiratory involvement (65.9% vs. 50.9%; p  = .05) and altered mental status (28.8% vs. 14.2%; p  < .01) were higher in the peri-post legalization period. The peri-post legalization period was characterized by more children younger than 12 years (12.1% vs. 3.0%; p  = .04), unintentional exposures (14.4% vs, 2.8%; p  = .002) and edibles ingestion (19.7% vs. 7.8%; p  = .01). Edible ingestion was an independent predictor of ICU admission (adjusted OR: 4.1, 95%CI: 1.2–13.7, p  = .02). Conclusions: The recreational cannabis legalization in Canada is associated with increased rates of severe intoxications in children. Edible ingestion is a strong predictor of ICU admission in the pediatric population.